Siderophore-Based Molecular Imaging of Fungal and Bacterial Infections-Current Status and Future Perspectives - Petrik, Milos; Pfister, Joachim; Misslinger, Matthias; Decristoforo, Clemens; Haas, Hubertus (Journal of fungi (Basel, Switzerland), 2020)
Invasive fungal infections such as aspergillosis are life-threatening diseases mainly affecting immuno-compromised patients. The diagnosis of fungal infections is difficult, lacking specificity and sensitivity. This review covers findings on the preclinical use of siderophores for the molecular imaging of infections. Siderophores are low molecular mass chelators produced by bacteria and fungi to scavenge the essential metal iron. Replacing iron in siderophores by radionuclides such as gallium-68 allowed the targeted imaging of infection by positron emission tomography (PET). The proof of principle was the imaging of pulmonary Aspergillus fumigatus infection using [68Ga]Ga-triacetylfusarinine C. Recently, this approach was expanded to imaging of bacterial infections, i.e., with Pseudomonas aeruginosa. Moreover, the conjugation of siderophores and fluorescent dyes enabled the generation of hybrid imaging compounds, allowing the combination of PET and optical imaging. Nevertheless, the high potential of these imaging probes still awaits translation into clinics.
Keywords: imaging; infection; fungal; siderophore; fluorescence; bacterial; positron emission tomography